2013
DOI: 10.1002/dvg.22362
|View full text |Cite
|
Sign up to set email alerts
|

Transposon mediated BAC transgenesis via pronuclear injection of mouse zygotes

Abstract: Pronuclear microinjection of bacterial artificial chromosomes (BACs) is the preferred way to generate transgenic mice because the transgene accurately recapitulates expression of the endogenous gene. However, the method is demanding and the integrity and copy number of the BAC transgene is difficult to control. Here, we describe a simpler pronuclear injection method that relies on transposition to introduce full-length BACs into the mouse genome. The bacterial backbone of a hPAX6-GFP reporter BAC was retrofitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…In case of a plasmid vector carrying the transposon unit, this means shortening the plasmid backbone. By placing the transposon TIRs next to one another, bacterial artificial chromosomes (BACs) over 100 kb in length have been demonstrated to transpose at reasonable efficiencies in human ES cells (Rostovskaya et al, 2012;Rostovskaya et al, 2013). The second mechanism limiting transposition of large constructs is a suicidal transpositional mechanism called autointegration .…”
Section: Cargo Capacitymentioning
confidence: 99%
“…In case of a plasmid vector carrying the transposon unit, this means shortening the plasmid backbone. By placing the transposon TIRs next to one another, bacterial artificial chromosomes (BACs) over 100 kb in length have been demonstrated to transpose at reasonable efficiencies in human ES cells (Rostovskaya et al, 2012;Rostovskaya et al, 2013). The second mechanism limiting transposition of large constructs is a suicidal transpositional mechanism called autointegration .…”
Section: Cargo Capacitymentioning
confidence: 99%
“…BAC DNA was prepared from bacterial culture grown at 30˚C using the Nucleobond BAC 100 kit (Macherey-Nagel), digested with MluI/AscI for removing the bacterial backbone, purified by Sepharose CL-4B chromatography (22), and injected (1-4 ng/ml) into the pronucleus of C57BL/6J fertilized oocytes. Offspring was genotyped using the primer pair 59-GCACGGTCAAGCTCATCTTCGCC-39 and 59-ATGCTCCTTCCAGGC-CCGCT-39.…”
Section: Generation Of Huxcr1 Transgenic Micementioning
confidence: 99%
“…The cargo capacity of the piggyBac transposon is fairly large; transposons with a cargo of up to 10 kb can be mobilized without losing transposition efficiency (62). Recently, it has been shown that piggyBac can transpose bacterial artificial chromosomes (BACs), which are 150 to 300 kb in length, in mouse and human pluripotent stem cells (50,63) and in mouse zygotes (64). In the best result in the zygote injection, 45% of F0 mice carried a BAC transgene and most of them have transposon signature (64).…”
Section: The Engineered Nonautonomous Piggybac Transposon Systemmentioning
confidence: 99%